ART use and associated factors among HIV positive caregivers of orphans and vulnerable children in Tanzania - Amon Exavery; John Charles; Asheri Barankena; Erica Kuhlik; Godfrey M. Mubyazi; Kassimu Tani; Amal Ally; Epifania Minja; Alison Koler; Levina Kikoyo; Elizabeth Jere (BMC, 2020)
Abstract Background Utilization of antiretroviral therapy (ART) is crucial for better health outcomes among people living with the human immunodeficiency virus (PLHIV). Nearly 30% of the 1.6 million PLHIV in Tanzania are not on treatment. Since HIV positive status is the only eligibility criterion for ART use, it is critical to understand the obstacles to ART access and uptake to reach universal coverage of ART among PLHIV. For the caregivers of orphans and vulnerable children (OVC) LHIV and not on ART, attempts to identify them and ensure that they initiate and continue using ART is critical for their wellbeing and their ability to care for their children. Methods Data are from the community-based, United States Agency for International Development (USAID)-funded Kizazi Kipya project that aims at scaling up the uptake of HIV/AIDS and other health and social services by orphans and vulnerable children (OVC) and their caregivers. HIV positive caregivers of OVC who were enrolled in the USAID Kizazi Kipya project between January 2017 and June 2018 were included in this cross-sectional study. The caregivers were drawn from 11 regions: Arusha, Iringa, Katavi, Kigoma, Mara, Mbeya, Morogoro, Ruvuma, Simiyu, Singida, and Tanga. The outcome variable was ART status (either using or not), which was enquired of each OVC caregiver LHIV at enrollment. Data analysis involved multivariable analysis using random-effects logistic regression to identify correlates of ART use. Results In total, 74,999 caregivers living with HIV with mean age of 44.4 years were analyzed. Of these, 96.4% were currently on ART at enrollment. In the multivariable analysis, ART use was 30% lower in urban than in rural areas (adjusted odds ratio (OR) = 0.70, 95% confidence interval (CI) 0.61-0.81). Food security improved the odds of being on ART (OR = 1.29, 95% CI 1.15-1.45). Disabled caregivers were 42% less likely than non-disabled ones to be on ART (OR = 0.58, 95% CI 0.45-0.76). Male caregivers with health insurance were 43% more likely than uninsured male caregivers to be on ART (OR = 1.43, 95% CI 1.11-1.83). Caregivers aged 40-49 years had 18% higher likelihood of being on ART than the youngest ones. Primary education level was associated with 26% increased odds of being on ART than no education (OR = 1.26, 95% CI 1.13-1.41). Conclusions Although nearly all the caregivers LHIV in the current study were on ART (96.4%), more efforts are needed to achieve universal coverage. The unreached segments of the population LHIV, even if small, may lead to worse health outcomes, and also spur further spread of the HIV epidemic due to unachieved viral suppression. Targeting caregivers in urban areas, food insecure households, who are uninsured, and those with mental or physical disability can improve ART coverage among caregivers LHIV.